Fabrication of a novel wound healing gel using Azadirachta indica and Chamaecostus cuspidatus formulation mediated calcium oxide nanoparticles - Raaj, T Arun; R, Subhashree.; Rajeshkumar, S; N, Thiyaneswaran (Journal of Neonatal Surgery, 2025)
Background: Wound healing has been a major focus of both traditional and modern medicine, with herbal medicines playing an important role in stimulating tissue repair and reducing inflammation. Herbal-based wound healing gels have grown in popularity due to their natural healing capabilities and lower risk of side effects compared to standard synthetic treatments. Usually, a blend of herbs with therapeutic properties, including neem and insulin plant, are used to make these gels. These herbs have anti-inflammatory, antibacterial, and antioxidant qualities that help speed up the healing process, relieve pain, and prevent infection. Aim: The goal of the current work is to make a gel based on Azadirachta indica and Chamaecostus cuspidatus mediated with calcium oxide nanoparticles for the post operative healing after a dental procedure. Materials and Methods: The solution contains calcium oxide nanoparticles infused in Azadirachta indica and Chamaecostus cuspidatus . The gel obtained was subjected to an anti-inflammatory test and membrane stabilisation. Results: The formed gel exhibited membrane stabilising activity at 50µL (82 %).They also show to be biocompatible and have anti-inflammatory properties. Conclusion: This novel synthesised wound healing gel may help to reduce the inflammation in the soft tissues and have good membrane stabilisation which in turn helps the patients undergoing dental procedures.